Handbook of practical program evaluation - Newcomer, Kathryn E. (Jossey-Bass, 2015)
The Handbook of Practical Program Evaluation provides tools for managers and evaluators to address questions about the performance of public and nonprofit programs. Neatly integrating authoritative, high-level information with practicality and readability, this guide gives you the tools and processes you need to analyze your program's operations and outcomes more accurately. This new fourth edition has been thoroughly updated and revised, with new coverage of the latest evaluation methods